Madame Prime Minister the story of Indira Gandhi - Garnett, Emmeline 1924- (New York Farrar, Straus & Giroux, 1967)
Biography of the first woman prime minister of India, Indira Gandhi, whose father, Jawaharlal Nehru, had governed India from its independence to his death in 1964.
Keywords: Gandhi, Indira Nehru -- 1917-1984 -- Juvenile literature; Gandhi, Indira Nehru -- 1917-1984.; Women prime ministers -- India -- Biography -- Juvenile literature; India -- Politics and government